Expression of microRNAs and their target genes in melanomas originating from gynecologic sites. - Mallory J DiVincenzo; Colin D Angell; Lorena P Suarez-Kelly; Casey Ren; Zoe Barricklow; Maribelle Moufawad; Paolo Fadda; Lianbo Yu; Floor J Backes; Kari Ring; Anne Mills; Craig Slingluff; et al. (PLoS ONE, 2023)
Melanomas from gynecologic sites (MOGS) are rare and have poor survival. MicroRNAs (miRs) regulate gene expression and are dysregulated in cancer. We hypothesized that MOGS would display unique miR and mRNA expression profiles. The miR and mRNA expression profile in RNA from formalin fixed, paraffin embedded vaginal melanomas (relative to vaginal mucosa) and vulvar melanomas (relative to cutaneous melanoma) were measured with the Nanostring Human miRNA assay and Tumor Signaling mRNA assay. Differential patterns of expression were identified for 21 miRs in vaginal and 47 miRs in vulvar melanoma (fold change >2, p<0.01). In vaginal melanoma, miR-145-5p (tumor suppressor targeting TLR4, NRAS) was downregulated and miR-106a-5p, miR-17-5p, miR-20b-5p (members of miR-17-92 cluster) were upregulated. In vulvar melanoma, known tumor suppressors miR-200b-3p and miR-200a-3p were downregulated, and miR-20a-5p and miR-19b-3p, from the miR-17-92 cluster, were upregulated. Pathway analysis showed an enrichment of "proteoglycans in cancer". Among differentially expressed mRNAs, topoisomerase IIα (TOP2A) was upregulated in both MOGS. Gene targets of dysregulated miRs were identified using publicly available databases and Pearson correlations. In vaginal melanoma, suppressor of cytokine signaling 3 (SOCS3) was downregulated, was a validated target of miR-19b-3p and miR-20a-5p and trended toward a significant inverse Pearson correlation with miR-19b-3p (p = 0.093). In vulvar melanoma, cyclin dependent kinase inhibitor 1A (CDKN1A) was downregulated, was the validated target of 22 upregulated miRs, and had a significant inverse Pearson correlation with miR-503-5p, miR-130a-3p, and miR-20a-5p (0.005 < p < 0.026). These findings support microRNAs as mediators of gene expression in MOGS.